A Validated Grading Scale for Downturned Oral Commisure in Asian Faces. Issue 7 (July 2021) - Lee, Jong Hun; Kim, Dong Gyu; Park, Eun Soo
Abstract : BACKGROUND: Downturned oral commissures develop gradually with aging. Tools have been developed to evaluate the marionette line or the lower face. However, there is no validated and reproducible tool to evaluate the progress after oral commissure treatment in clinical practice. OBJECTIVE: The authors aimed to develop a scoring system to evaluate therapeutic interventions for downturned oral commissures and to verify its reliability, reproducibility, and clinical significance. METHODS AND MATERIALS: In the Scale Development Group, the Delphi method was used to establish a 5-graded scoring system to evaluate oral commissure position. The scoring system was applied to 50 participants. The authors recorded and compared the intrarater agreement, interrater agreement, and significance of the grade-dependent scale. RESULTS: Delphi analysis of the scoring system verified the grade description adequacy. Intrarater agreement showed almost perfect agreement, and the intraclass correlation coefficient of the interrater agreement had a significantly higher agreement rate. The differences between the clinical grades were significant. CONCLUSION: The Hugel Downturned Oral Commissure Scale is precise, reproducible, and reflective of the clinical differences for downturned oral commissure. Its novelty lies in the use of specific angles and ratio. This scale has clinical trial potential owing to its standardized and quantitative assessment. Abstract : Supplemental Digital Content is Available in the Text.